Modern windows hibernation file analysis. (March 2017) - Sylve, Joe T.; Marziale, Vico; Richard, Golden G.
Abstract: This paper presents the first analysis of the new hibernation file format that is used in Windows versions 8, 8.1, and 10. We also discuss several changes in the hibernation and shutdown behavior of Windows that will have a direct impact on digital forensic practitioners who use hibernation files as sources of evidence.